(Post)utopian Vineland: Ideological Conflicts in the 1960s and the 1980s - Lovorka Gruic Grmusa (European Journal of American Studies)
This paper delineates a revolutionary period in postmodern America: the sixties from the vantage point of the eighties as presented in Thomas Pynchon’s Vineland. It brings controversial aspects of U.S. history and culture into view: the blacklist period in the 1950s, the rise of counterculture and the hippie movement, and the politics of the eighties. With their arrival, each new generation pushes aside the old and implements their own ideologies, which gives this space (Vineland and the U.S. in general) utopian and post-utopian characteristics at the same time. It is a crossroads which generation after generation has inhabited, with layers of history that overlap, underlying the ideological battles between woge and humans, Indians and the whites, the Left and the Right, hippies and the Nixon administration, various marginal groups (mostly reminders of the hippy generation) and the Reaganite politics.